Perancangan Interior Restoran China di Surabaya - Novia Agatha Putri; Stephanus P Honggowidjaja; Priyo Suprobo (Intra, 2018)
The design aims to solve the existing problems: 1) the lack of Chinese cultural elements and characteristics, 2) the absence of space to welcome guests such as lobby, and 3) the use of monotonous furnitures. Based on those problems, designer learns how to create an interesting, warm and cozy Chinese restaurant atmosphere with Chinese characteristics that is able to maximize the functionality of each room within the restaurant. The interior design of this Chinese restaurant located in Surabaya is also act as an introduction to modern Chinese culture towards society. Design Thinking method is used to get the maximum result during the design process. The design results in the establishment of a lobby facility, a semi-VIP area that offers scenic view, VIP rooms as private areas, the stage to accommodate music and dance performances, buffet area, and bar. In the end, hopefully the design of this Chinese restaurant could be an alternative solution to resolve the existing problems, especially in Surabaya.